The Effect of Code Mixing Technique to Students’ Speaking Skill at SMK Prima Bekasi - Muhamad Kholil (INDO PUBLISHING, 2025)
The objective of research is to study effect of code-mixing technique to student speaking skill at SMK PRIMA BEKASI. The purpose of this study is to find out whether this language mixing technique had a significant influence on students' speaking ability. This research was done by using experimental research. This research involves X-A and X-B classes at SMK PRIMA BEKASI Jl. Swadaya I No.33, Jatimurni, Kecamatan Pondok Melati, Kota Bekasi, Jawa Barat. 17431. The sample of this study consist of 2 classes, such as X-A and X-B classes. X- A class is a class that is treated by using the code-mixing technique (as experimental class), while X-B class is a class that was not treated by the code-mixing technique (as the controlled class ) both techniques are compared and was found out the influence of the code - mixing technique. The results of this study prove that students' scores in learning to speak English by using code mixing techniques are improved well than without using code mixing. It can be concluded that the code-mixing technique is effective in teaching English because it shows a significant influence on the speaking ability of class X of SMK Prima Bekasi with a medium significant scale. The results showed that student learning outcomes taught by code mixing method were significantly improve better than students who taught without using code mixing method. Result of this research give important meaning for the development of policy of education, specially related to make up of the quality of Student’s Learning Achievement.